Surface EMG analysis of weakness distribution in upper limb muscles post-stroke - Lv, Wenwen; Liu, Kai; Zhou, Ping; Huang, Fei; Lu, Zhiyuan (Frontiers in Neurology, 2023)
Weakness is a common symptom after stroke. This study aims to depict weakness distribution among forearm muscles given that joints in the upper limb are usually driven by a group of muscles. Multi-channel EMG was applied to assess the muscle group, and an EMG-based index was proposed to quantify weakness of individual muscles. By using this method, four weakness distribution patterns were observed in extensor muscles from 5 out of 8 subjects after stroke. Complex weakness distribution patterns were observed in flexor muscles from 7 out of the 8 subjects when they perform grasp, tripod pinch, and hook grip. The findings can help determine the weak muscles in clinic, and facilitate development of appropriate interventions in stroke rehabilitation targeting specific muscle weakness.